The Effect of Reward, Punishment and Motivation Work on The Performance of Employees Cv. Rizki Agung Surabaya - Elok Sekar Sari; Elok Damayanti; Putri Rosalina Rahmawati (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
The purpose of this research is to find out how much influence reward, punishment, and work motivation simultaneously and also parsia have on the performance of CV employees. Rizki Agung Surabaya. This study uses quantitative methods by distributing questionnaires to employees of CV. Rizki Agung as a respondent. Determination of the sample was carried out using the Saturated Random technique as many as 54 samples. Hypothesis analysis and testing was done by using multiple linear regression method. Regression analysis results in the equation Y = 9.867 + 0.2461 + 0.3092 + 0.2043 which shows that simultaneously the dimensions of reward, punishment, and work motivation have a positive direction on employee performance. The F test shows that the calculated F is (3.588) > Ftable (2.54) which means that the variables of reward, punishment and work motivation have a significant simultaneous effect on employee performance. The t-test shows that the variable X1 (Reward) with a t-count value of 1.046 > t-table with a significant level (0.305) has the largest significant partial effect on employee performance. The variables of punishment and work motivation have a partial but not significant effect on employee performance.